2023
DOI: 10.3389/fphys.2023.1156913
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule inhibitors of osteoarthritis: Current development and future perspective

Abstract: Osteoarthritis (OA) is one of the common degenerative joint diseases in clinic. It mainly damages articular cartilage, causing pain, swelling and stiffness around joints, and is the main cause of disability of the elderly. Due to the unclear pathogenesis of osteoarthritis and the poor self-healing ability of articular cartilage, the treatment options for this disease are limited. At present, NSAIDs, Glucocorticoid and Duloxetine are the most commonly used treatment choice for osteoarthritis. Although it is som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…Besides intra-articular delivery, transdermal drug delivery is also an efficient method [92,93]. However, transdermal medications are limited to those that alleviate symptoms but do not alter disease progression or repair cartilage [94]. Some medications may have side effects, like gastrointestinal issues with NSAIDs or joint destruction risks with glucocorticoids.…”
Section: Medicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides intra-articular delivery, transdermal drug delivery is also an efficient method [92,93]. However, transdermal medications are limited to those that alleviate symptoms but do not alter disease progression or repair cartilage [94]. Some medications may have side effects, like gastrointestinal issues with NSAIDs or joint destruction risks with glucocorticoids.…”
Section: Medicationmentioning
confidence: 99%
“…PRP, an autologous blood product derived from the patient's own blood, offers high safety and minimal side effects [95,96]. PRP contains bioactive factors like platelet-derived growth factor (PDGF), transforming growth factor β (TGF-β), insulin-like growth factor (IGF), and fibroblast growth factor (FGF), crucial for regulating chondrocyte survival and metabolism [94]. Studies indicated that PRP promoted chondrocyte proliferation and matrix production while reducing inflammation [97][98][99].…”
Section: Platelet-rich Plasma Therapymentioning
confidence: 99%
“…Although the OA disease phenotype remains ambiguous, many animal and clinical trials have shown that targeting the early activation of osteoclasts can block the abnormal reconstruction of SB, thereby preventing articular cartilage degeneration. [12] Mitochondrial reactive oxygen species (ROS), as secondary messengers, initiate the differentiation of hematopoietic stem cell or monocyte/macrophage progenitor cells into osteoclasts. [13] Currently, Targeting mitochondria-generated ROS effectively inhibits osteoclast activation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the OA disease phenotype remains ambiguous, many animal and clinical trials have shown that targeting the early activation of osteoclasts can block the abnormal reconstruction of SB, thereby preventing articular cartilage degeneration. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%